1991
DOI: 10.2307/1485911
|View full text |Cite
|
Sign up to set email alerts
|

Marsh Foraminifera and Arcellaceans of the Lower Mississippi Delta: Controls on Spatial Distributions

Abstract: Foraminifera and arcellaceans ("thecamoebians") were examined from 73 surface samples collected to represent four vegetation zones (I-IV) that have been defined in the Mississippi Delta Plain. Previous studies of benthonic foraminifera had not differentiated these environments. Saline marshes (I) are characterized by a vertical zonation typical of most marshes, with a variety of estuarine species in the low marsh and trochamminids in the upper marsh. Brackish marshes (II) are dominated by a completely differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 28 publications
1
28
0
1
Order By: Relevance
“…Foraminifera were concentrated from 3-cm 3 bulk sediment samples by washing the material over 500 µm and 32 µm sieves and retaining the particles in this size range. When foraminiferal abundance was sufficient, up to 300 specimens were tallied from the remaining 32 µm to 500 µm fraction, and benthic species were identified using criteria provided by Phleger (1965), Scott et al (1991), Javaux andSen Gupta (1999).…”
Section: Sedimentary Analysismentioning
confidence: 99%
“…Foraminifera were concentrated from 3-cm 3 bulk sediment samples by washing the material over 500 µm and 32 µm sieves and retaining the particles in this size range. When foraminiferal abundance was sufficient, up to 300 specimens were tallied from the remaining 32 µm to 500 µm fraction, and benthic species were identified using criteria provided by Phleger (1965), Scott et al (1991), Javaux andSen Gupta (1999).…”
Section: Sedimentary Analysismentioning
confidence: 99%
“…Subsamples of these surface samples were analysed for microfossils (foraminifera, arcellacians, large tintiniids, diatoms and ostracods) and for palynomorphs, including pollen and spores, dinoflagellate cysts, acritarchs and freshwater algal spores, fungal spores and reworked pre-Quaternary palynomorphs. The microfossil subsamples were processed by wet sieving on a 63-m sieve and by microscope examination in water, following the method of Scott et al (1991). The palynology samples were processed by standard methods for Quaternary marine sediments, as outlined herein.…”
Section: Palynology and Micropalaeontologymentioning
confidence: 99%
“…Testate amoebae also have been reported in coastal environments, most notably in saltmarshes (e.g. Scott et al, 1977Scott et al, , 1991Scott et al, , 1995Medioli and Scott, 1983;Charman et al, 1998Charman et al, , 2000bCharman et al, , 2002Gehrels et al, 2001) and coastal basins (Patterson et al, 1985;Lloyd, 2000). Until recently, however, these limited studies of coastal thecamoebians generally had been based on the larger specimens found in the size range routinely analysed for foraminiferal analysis (63-500 µm) (e.g.…”
Section: Introductionmentioning
confidence: 99%